Implementasi Microteaching Berbasis Critical Thinking Pedagogy pada Calon Guru PAUD - Gina Asri Ruwaida; Mariana Panji Ramadan; Listian Indriyani Achmad; Siti Kholifah (Yayasan Azhar Amanaa Yogyakarta, 2026)
Critical-thinking-oriented learning in early childhood education requires prospective teachers to translate reasoning skills into developmentally appropriate dialogue and exploration. This study aimed to describe the implementation of microteaching based on Critical Thinking Pedagogy among prospective early childhood teachers. Unlike conventional microteaching that commonly emphasizes general teaching performance, this approach positioned open-ended questioning, response elaboration, feedback, reflection, and re-teaching as the core of the practice cycle. A descriptive qualitative case study involved 20 students in a one-month program consisting of four meetings. Data were collected through classroom observations, learning-activity plans, reflective responses, and group interview notes, then analyzed thematically. The findings showed that open-ended questioning became the main feature of practice. Student engagement was evident in active participation, note-taking, revision of activity plans, and willingness to repeat teaching segments. Reflection strengthened their orientation toward improving teaching, while time management remained the primary challenge. Students also perceived the approach as applicable to future field practice. The study concludes that Critical Thinking Pedagogy-based microteaching provides a structured space for dialogic practice, feedback, reflection, and preparation for classroom implementation. Practically, teacher education programs can integrate this cycle into learning-design, microteaching, and teaching-practicum courses and assess the quality of interaction alongside general teaching skills.